Liver transplantation for combined hepatocellular‐cholangiocarcinoma: Outcomes and prognostic factors for mortality. A multicenter analysis. Issue 2 (15th January 2021) - Jaradat, Derar; Bagias, Georgios; Lorf, Thomas; Tokat, Yaman; Obed, Aiman; Oezcelik, Arzu
Abstract: Introduction: Combined hepatocellular‐cholangiocarcinoma is rare and comprises features of hepatocellular carcinoma and cholangiocarcinoma. The treatment of choice has not yet been defined. The aim of the study was to analyze outcomes of patients with combined hepatocellular‐cholangiocarcinoma, who underwent liver transplantation. Material and Methods: All patients with combined hepatocellular‐cholangiocarcinoma, who underwent liver transplantation, from January 2001 to August 2018 were identified. Pre‐, intra‐ and postoperative data were retrospectively assessed. A univariate analysis was performed to identify prognostic factors. Results: A total number of 19 patients were included to this study. Perioperative death was seen in two patients (10.5%). Recurrent disease was reported in 11 patients (64.7%) within the median time of 4 months. One and three years survival rates were 57.1% (CI 0.301–1) and 38.1% (CI 0.137–1). Factors associated mortality were tumor size >3 cm, presence of lymphatic invasion, and prolonged ICU stay. Patients with mixed HCC‐CC lesions have significantly better survival compared to patients with separate lesions of HCC and CCC in one liver ( p  = .025). Conclusion: Although overall survival rates are clearly decreased compared to HCC patients, liver transplantation should be taken under consideration for selected patients with early stage and real mixed HCC‐CC, who are likely to benefit from liver transplantation.